2021
DOI: 10.3390/ma14237215
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy of a Diode Laser on Titanium Implants for the Reduction of Microorganisms That Cause Periimplantitis

Abstract: The paper presents the optimisation of a safe diode laser irradiation process applied to the surface of titanium implants in order to reduce microbial numbers in the treatment of inflammation classified as periimplantitis. The study comprised isolation and identification of microorganisms inhabiting surfaces of dental implants, crowns, teeth and saliva from patients with fully symptomatic periimplantitis. Microorganisms were detected by a culture-dependent method and identified with the use of MALDI-TOF mass s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…One of the methods that can reduce the number of microorganisms on the composites’ surface is the use of a diode laser, the irradiation of which can supplement the implantological treatment procedure. The effectiveness of the diode laser against microorganisms inhabiting porcelain, zircon, and titanium was confirmed by Wawrzyk et al [ 20 , 21 , 22 ]. The method of decontamination with the diode laser used by Wawrzyk et.al.…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…One of the methods that can reduce the number of microorganisms on the composites’ surface is the use of a diode laser, the irradiation of which can supplement the implantological treatment procedure. The effectiveness of the diode laser against microorganisms inhabiting porcelain, zircon, and titanium was confirmed by Wawrzyk et al [ 20 , 21 , 22 ]. The method of decontamination with the diode laser used by Wawrzyk et.al.…”
Section: Introductionmentioning
confidence: 83%
“…These parameters allow for a comprehensive assessment of the surface microgeometry of the tested materials. Surface microgeometries are usually described by the following roughness parameters: Ra, arithmetic mean of the elevation profile; Rq, the mean square elevation profile; Rt, the height of the highest peak profile; and Ry, the lowest recesses’ profile [ 21 ]. The roughness parameters of the composites used in dentistry depend, among others, on the material and its processing.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, a recent study has shown that the repeated application of diode laser on titanium implants has eradicated all the microorganisms in more than two-thirds of the sample without changing the quality of the implant surface. 46 In the same context, Mettraux et al 47 showed that repeated diode laser application following mechanical debridement in the management of peri-implantitis lesions resulted in a significant improvement in the periodontal parameters for at least 2 years. Moreover, temperature rise above critical threshold of 10 ℃ after 18 seconds of application 48 , 49 could be an associated issue of concern.…”
Section: Discussionmentioning
confidence: 99%
“…Excessive plaque deposition, which is not beneficial for dental implants, is favoured by an increase in the roughness of implant-prosthetic surfaces [ 57 , 58 ]. However, some researchers proved that there is no evidence that oral implant surfaces show a relationship between the biofilm development and the surface roughness [ 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…One such method is laser irradiation, which has become more and more common in dentistry for the decontamination of microbiologically contaminated surfaces. Very good results in the reduction in the number of microorganisms were achieved cleaning implants with a diode laser with a wavelength of 810 nm at the optimised doses [ 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%